The Choice of Environmental Management Accounting Practices Adopted by Managers: Evidence from the Hotel Sector in KwaZulu Natal, South Africa - Thomas Nyahuna (CV. Literasi Indonesia, 2022)
To understand the ways that 5-star hotels in Kwazulu Natal use to select environmental management accounting (EMA) practices to implement, the study assists hotel managers in better understanding and effectively formulating other mechanisms for improving EMA. The paper ascertains the manner applied by managers in 5-star hotels in KwaZulu Natal province when selecting EMA practices to adopt for their business activities. To attain the key aim objective of the research, 21 interviews and observations were conducted on three 5-star hotels among hotel managers, accountants, and administration managers. The study identifies that meeting international customers’ expectations plays a dominant role in pushing hotels to select EMA practices that can be easily identified by the customers such as water and energy efficiency. 78% of the interviewees endorse that international clients choose hotels that promote environmental initiatives hence the choice of current EMA practices. In addition, this is critical because it also affects the financial performance of the hotels. The paper provides further empirical evidence in extant literature that financial performance remains the key factor influencing a decision on EMA practices to be applied by hotels in emerging markets.